The impact on blood donor screening for human immunodeficiency virus, hepatitis C virus, and hepatitis B virus using plasma from frozen‐thawed plasma preparation tubes. Issue 2 (12th October 2015) - Allison, Kirsty M.; Faddy, Helen M.; Margaritis, Angelo; Ismay, Susan; Marks, Denese C.
Abstract : BACKGROUND: Blood services are required to maintain repositories of frozen samples for confirmation of results and/or retrospective testing. The Australian Red Cross Blood Service archives donor samples in plasma preparation tubes (PPTs). This study aims to evaluate the effect of freeze‐thawing and extended frozen storage on the ability to detect human immunodeficiency virus (HIV), hepatitis C virus (HCV), and hepatitis B virus (HBV) using blood donation screening assays in samples stored in PPTs. STUDY DESIGN AND METHODS: Whole blood was spiked with HIV‐, HCV‐, or HBV‐reactive plasma at high and low viral loads and stored in PPTs or as plasma aliquots. All samples were frozen and stored at not more than −30°C. At 0, 3, 6, 12, 18, and 36 months, samples were tested for HIV and HCV antibodies, HBV surface antigen, and viral nucleic acid. Additional samples were thawed and refrozen either once or twice before testing to simulate up to three freeze‐thaw cycles. RESULTS: All PPT and plasma aliquots retained appropriate viral reactivity, including those with multiple freeze‐thaw cycles, on both nucleic acid testing and serology platforms. CONCLUSION: Frozen storage of biologicals in PPTs, as opposed to plasma aliquots, does not affect the ability to detect HIV, HCV, and HBV using viral nucleic acid or serology donation screening systems for up to 36 months. Freezing and thawing PPT samples did not impact the ability to detect these viruses. Our study demonstrates that PPTs appear to be an appropriate receptacle for frozen plasma sample archiving for up to 3 years.